Perkiraan Tegangan Lewat Denyar Isolator Tegangan Menengah 20 kV Keramik dan Resin Epoksi berdasarkan Data Arus Bocor - Valdi Rizki Yandri; Herisajani Herisajani; Fitriadi fitriadi (Teknik Elektro Politeknik Negeri Padang, 2019)
This paper explains the research results of leakage current data and estimation of flashover voltage on ceramics and epoxy resin as 20 kV outdoor insulator in a chamber with tropical climate conditions. The waveform of leakage current (LC) was measured using a digital oscilloscope. The digital data was transferred to a personal computer using a RS-232 cable. The digital data was analyzed using Fast Fourier Transform. The result showed that LC was affected by various environment conditions like temperature, humidity and pollution. LC of ceramics insulator was higher than epoxy resin insulator in low temperature, high humidity and high pollution condition.